Increment of body mass index is positively correlated with worsening of endothelium-dependent and independent changes in forearm blood flow - Kraemer-Aguiar, Luiz G.; Miranda, Marcos L.; Bottino, Daniel A.; Lima, Ronald A.; Souza, Maria das Graças C.; Balarini, Michelle M.; Villela, Nivaldo R.; Bouskela, Eliete (Frontiers in Physiology, 2015)
Obesity is associated with the impairment of endothelial function leading to the initiation of the atherosclerotic process. We have hypothesized that an increasing impairment of endothelial and vascular smooth muscle cell functions occurs from lean subjects to severe obese ones. Thus, the present study was carried out to investigate the grade of obesity in which endothelial dysfunction can be detected and if there is an increasing impairment of endothelial and vascular smooth muscle cell functions as body mass index increases. According to body mass index, subjects were allocated into five groups: Lean controls, Overweight, Obese class I, Obese class II, and Obese class III. Endothelial and vascular smooth muscle cell functions were evaluated measuring forearm blood flow responses to increasing intra-arterial infusions of acetylcholine and sodium nitroprusside using venous occlusion plethysmography. We observed that forearm blood flow was progressively impaired from lean controls to severe obese and found no significant differences between Lean controls and Overweight groups. Our data suggests that obesity class I is the first grade of obesity in which endothelial dysfunction can be detected and that body mass index positively correlates with the worsening of endothelium-dependent and independent changes in forearm blood flow.